Konsep Dasar Pendidikan Agama Islam - Yasmansyah, Yasmansyah; Husni, Arman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The basis of Islamic education is based on the Al-Quran and Hadith, these two pillars are built onthe basic concept of Islamic education, the starting point of which is the human concept according to Islam. The purpose of writing this article is to provide an overview of the basic concepts of Islamic education with sub-chapters consisting of the nature of Islamic education, basic concepts of Islamic education, goals and principles in Islamic education. This research is a library research, namely research that is sourced from library materials using a qualitative approach. In this case, the researcher explored a number of data, both primary data and secondary data with the following steps: reading and studying in depth primary data such as books, journals, articles, theses, theses and dissertations related to the discussion of the basic concepts of education. Islam. The results of the discussion show that Islamic education is a conscious effort in the form of direction, guidance and training for students, so that they become Muslim individuals as much as possible in accordance with the guidance of the Qur'an and hadith. The concept of Islamic education is formal Islamic education and non-formal Islamic education and informal Islamic education. The purpose of Islamic education includes two main aspects, namely realizing happiness in life in this world and happiness in the hereafter.